Promising new fixed combination for the treatment of diseases of the hepatobiliar system: Substantiation of pharmacotherapeutic properties and pharmaceutical quality profile - Bondarenko, L. B.; Gorchakova, N. O.; Golembiovska, O. I.; Galkin, O. Y. (Regulatory Mechanisms in Biosystems, 2018)
In this review article an analysis of literature data on the pharmacological and clinical study of a fixed combination of medicinal substances (artichoke leaf extract, ursodeoxycholic acid, taurine, and Angelica sinensis roots extract), as well a scientific substantiation of the pharmaceutical quality profile of the corresponding finished solid dosage form has been conducted. Chronic diseases of the hepatobiliary system are some of the most common human diseases and inferior only to atherosclerosis . The fact that cholecystectomy is the most common surgical operation in the abdominal organs is evidenced by the widespread distribution of the pathology of the biliary system. The fact that there is an increasing number of diagnoses of cholelithiasis in children and infants is a cause for concern. Diseases of the biliary system are closely related to violations of the functional state of the liver. Synthesis of cholesterol supplemented bile with reduced bile acid content significantly increases the risk of gallstones, as well as gallbladder cholesterol. We have substantiated that the developed preparation is a fixed combination of medicinal substances with well-researched medical applications in the treatment of dyspeptic disorders with functional disorders of the biliary system, biliary dyskinesia of the hypokinetic type, and gastritis with reflux of bile. Each of the components of the fixed combination has an important influence on the human hepatobiliary system. The effect of ursodeoxycholic acid is due to the relative replacement of lipophilic toxic bile acids, improving the secretory capacity of hepatocytes and immunoregulatory processes, which is especially important in liver and cholestatic diseases. Taurine is a synergist of ursodeoxycholic acid, since it forms biliary conjugates in the liver. The artichoke extract has choleretic, hepatoprotective and diuretic effects, while the A. sinensis roots extract demonstrates moderate spasmolytic and anti-inflammatory properties. We conducted a general description of active pharmaceutical ingredients and a review of biopharmaceutical tests, analyzed relevant pharmacokinetic and pharmacodynamic studies, and summarized the results of clinical efficacy and safety trials. Particular attention is paid to the results of clinical studies of the developed fixed combination. It should be noted that artichoke leaf extract, ursodeoxycholic acid, and taurine are widely used throughout the world in official medicine, at the same time, A. sinensis roots extract is more widely used in traditional Chinese medicine. The fixed combination has a favorable safety profile, is investigated in clinical conditions in vivo both in the form of individual components and in the form of a single drug. A fixed combination pharmaceutical profile is based on the general requirements for solid dosage forms, as well as experimentally substantiated specific indicators and research methods.